Efeito do protocolo de tratamento de superfície para reparo de restaurações em resina composta na resistência de união e rugosidade superficial - Maia, Thaís Souza (2018)
The aim of this study was to evaluate the bond strength and surface roughness of composite resin restoration repair submitted to different surface treatments. Eighty resin composite specimens (10x10x2mm) were prepared, aged by artificial saliva and randomly divided into eight groups according to the type of surface treatment: phosphoric acid and adhesive (AcA), abrasion bur, phosphoric acid and adhesive (PdAcA); abrasion bur, phosphoric acid, silane and adhesive (PdAcSA); abrasion bur, phosphoric acid and experimental primer (PdAcP); air-abrasion with Al2O3, phosphoric acid and adhesive (JAcA); Al2O3, phosphoric acid, silane and adhesive (JAcSA); Al2O3, phosphoric acid and experimental primer (JAcP) phosphoric acid and adhesive and no aged resin (control group). The repair cylinders were built up on their surfaces and analysed by a microshear test (μTBS) and failure mode. Eighty additional specimens (4x2mm) were made to be analysed surface roughness quantitatively (Ra/μm) (n=10). Representative specimens of surface treatments and additionals were analysed qualitatively by scanning electron microscope (SEM). Data were statistically analyzed at α = 0.05. The highest values were found to the JAcSA (19.49 ± 1.57), followed by PdAcSA (16.59 ± 2.78), and JAcA group (16,080 ± 3,295). The lowest bond strength value was observed to the control group (10,601 ± 2,773), where no mechanical treatment and aging was done. Experimental primer did not improve the bond strength of composite repair. JAcP, PdAcP showed higher values of surface roughness and significant difference in relation to all other groups (p>0.001). In general, adhesive failures were predominant, followed by mixed, and only the PdAcSA group presented a predominant aged cohesive failure. Mechanical surface treatment of composite resin repair significantly improves the bond strength. However, protocol that is more effective was found to the association with chemical treatments: silane and adhesive application regardless of the mechanical treatment used and the application of the experimental primer provided higher values of roughness surface, but did not improve the bond strength to microshear.